Meanings and images on the political discourse of liberalism and conservatism in liberal Costa Rica: an incisive look from the province of Cartago and the "national" context regarding the conceptual discussion of both notions (1889-1914) - Gómez Solano, Juan Alberto (2022)
The article presents the set of meanings and social representations that were formed around the discussion of the liberal-conservative concepts for the Costa Rican case, during the twilight of the nineteenth century and the early twentieth century, which were marked by a convulsive and unequal political-electoral and sociocultural environment within Costa Rican society. This was due to tensions that arose between liberals and conservative popular sectors that were supported by the Catholic Church. The text develops the subject following an approach based on the relational analysis of spatial scales derived from Italian microhistory, that is, from the local to the "national" stage, taking as a starting point the particular case of the province of Cartago and how, from the Carthaginian environment, it connects with the discussion of both political notions at a national level.